Service level agreement : a complete guide - 2019 edition - Blokdijk, Gerard (Unidentified 5STARCooks, 2018)
A professional technical roadmap to IT Service Level Management & Agreements, Service Design & Continual Service Improvement with design, role & responsibility, KPI, communication plan & SLA template resources for organizational implementation.
Includes index.
oif 23/01/2020
Loans
Keywords: Service industries--Cost control; Service industries--Quality control; Service-level agreements; Total quality management